The Effect of Tax Planning on Company Value in Manufacturing Companies in the Food and Beverage Sector Listed on the IDX - Junaid, Asriani; Saleh, Mushlih (Fakultas Ekonomi & Bisnis Universitas Muslim Indonesia, 2024)
This study aims to determine the influence of Tax Planning on Company Value. Tax Planning is used as an independent variable and Company Value as a dependent variable. The population in this study is food and beverage companies listed on the Indonesia Stock Exchange in 2018-2012. The sample consists of 6 companies with a period of 5 years. namely: Wilmar Cahaya Indonesia Tbk, Nippon Indosari Corporindo Tbk, Sekar Bumi Tbk, Sekar Laut Tbk, Siantar Top Tbk, and Ultrajaya Milk Industry and Trading Company, Tbk. The sample selection method is purposive sampling. The type of data used is quantitative data and data sources using secondary data. The analysis method used to test the hypothesis is to use simple linear regression analysis. The results show that tax planning does not have a significant effect on the Company's Value.